Mentored Research in a Tribal College Setting: The Northern Cheyenne Case - Carol Ward; Kacey Widdison Jones; Ryan Coles; Loren Rich; Stan Knapp; Robert Madsen (Journal of Research in Rural Education, 2014)
The current study, which focuses on mentored research experiences of freshmen and sophomores at the tribal college of the Northern Cheyenne Nation, responds to the call by Ovink and Veazey (2011) for additional study of effective strategies for providing both mentoring and research experiences for minority undergraduates. We use qualitative data"interviews and observations"to explore the meanings rural tribal college students give to their mentored research experiences and the impact on their academic plans. Findings show that effective mentors develop trust and support for student learning and their personal goals. The data also suggest that successful mentoring strategies facilitate learning by doing and relating to the student's worldview and context. Additionally, non-native instructors who engage in authentic, caring interactions with students can successfully mentor native students in a supportive tribal college context. Tribal college students indicate that, similar to many American Indian university students, they want to return to their reservation communities following completion of college. However, tribal college students bring these interests into their academic plans as freshmen and sophomores. We conclude that appropriate mentoring relationships and relevant research experiences empower tribal college students to pursue their academic goals both in and outside their community as well as prepare to return.